1998
DOI: 10.1002/hep.510280606
|View full text |Cite
|
Sign up to set email alerts
|

Kai1, A New Metastasis Suppressor Gene, Is Reduced in Metastatic Hepatocellular Carcinoma

Abstract: Down-regulation of KAI1 expression has been shown to be associated with formation of metastases or disease progression in prostate and pancreatic cancer. In the present study we analyzed the expression pattern of KAI1 in metastatic and nonmetastatic hepatocellular carcinomas (HCCs) in comparison with normal livers to evaluate whether alteration of KAI1 also facilitates the metastatic ability in this malignancy. Thirty-nine primary HCCs and 10 normal liver tissue samples were studied for KAI1 messenger RNA (mRN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
42
1
1

Year Published

1999
1999
2007
2007

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(47 citation statements)
references
References 29 publications
3
42
1
1
Order By: Relevance
“…However, recently, RUVBL2 was also found to be required for the repressing effect of ␤-catenin on the transcription of the antimetastatic gene KAI-1, 36 which is frequently down-regulated in HCC. 37 In our study of a large number of HCC samples, there were, however, no correlations between the levels of expression of RUVBL2 and ␤-catenin target genes. It is thus likely that additional mechanisms, independent of ␤-catenin, may also explain the oncogenic properties of RUVBL2.…”
Section: Discussioncontrasting
confidence: 56%
“…However, recently, RUVBL2 was also found to be required for the repressing effect of ␤-catenin on the transcription of the antimetastatic gene KAI-1, 36 which is frequently down-regulated in HCC. 37 In our study of a large number of HCC samples, there were, however, no correlations between the levels of expression of RUVBL2 and ␤-catenin target genes. It is thus likely that additional mechanisms, independent of ␤-catenin, may also explain the oncogenic properties of RUVBL2.…”
Section: Discussioncontrasting
confidence: 56%
“…Inactivation of the gene that encodes the integral membrane protein, KAI-1, which appears to function in cell-cell and cell-extracellular matrix interactions, is strongly down-regulated in metastatic HCC nodules (Guo et al, 1998) as well as other metastatic tumor types (Dong et al, 1995), suggesting that KAI-1 is a tumor suppressor whose integrity prevents metastasis. Increased expression of other oncogenes has also been documented in large tumors.…”
Section: Late Events In Hepatocarcinogenesis (Tumor Progression and Mmentioning
confidence: 99%
“…On the other hand, oncogenes and certain cell cycle controllers, such as c-myc (Wu et al, 1996), c-Jun, c-fos (Twu et al, 1993), c-met (Boix et al, 1994;Grigioni et al, 1995), cets-1 (Ozaki et al, 2000), cyclin D1 (Peng et al, 1998;Deane et al, 2001;Joo et al, 2001), cyclin E (Peng et al, 1998), and gankyrin (Higashitsuji et al, 2000), were overexpressed or re-expressed in the later stage of hepatocellular carcinogenesis. Finally, some genes involved in cell-cell or cell-extracellular matrix interactions, such as MMPs (Arii et al, 1996), integrin a6b1 (Begum et al, 1995), syndecan-1, nm23 (Fujimoto et al, 1998), and KAIL (Guo et al, 1998), were reported to play important roles in HCC progression due to correlation with invasive and metastatic potentials.…”
Section: Introductionmentioning
confidence: 99%